Визначення чутливості динамічних та міцнісних характеристик тонкостінних елементів машинобудівних конструкцій - Танченко, Андрій; Ткачук, Ганна; Ткачук, Антон (КІНПАТРІ ЛТД, 2013)
For determination of sensitiveness of stressed-deformed state and vibrations eigenfrequencies of thinwalled elements of machine-building constructions on the change of their thickness it is suggested to apply procedure of direct eventual indignation of their finite-element models. It provides exactness of approximation dependences for considerably greater range of thin-walled elements thickness varying.
Determination of sensitiveness of dynamic and strength characteristics of thin-walled elements of machine-building constructions